Menards' St. Mary's County Tract Map of 1705 (1973) - Russell Menard (1973)
In early 1971 the St. Mary's City Commission, with funds provided by the Jacob and Anita France Foundation, retained me [Russell Menard] to study landholding. settlement patterns and population growth in seventeenth century St. Mary's County. Part of the task was to complete a tract map started by Ms. Barbara Lathroum during the previous summer. The procedure followed was simple. All of the nearly 500 surveys listed in the 1705 rent roll for the county were located in the patent books and transcribed on to index cards. The surveys were then drawn on the map. Given the quality of seventeenth century surveying, the project was a success. 425 tracts (85% of the total) were located on the map. The placement of the tracts should be considered tentative in all cases, but the map provides a useful tool for students of the county's past. Certainly it is accurate enough to determine hundred boundaries, settlement patterns and the approximate place of residence of many seventeenth century inhabitants. More work is needed, but the map is adequate for most purposes if precise location to a boundary relative to present day features is not required. (From May 1973 Chronicles of St. Mary's. See this issue for the published mpa, more details and listing of all tracts.)